PETROFABRICS AND SEISMIC PROPERTIES OF GARNET PERIDOTITE FROM THE UHP SULU TERRANE (CHINA): IMPLICATIONS FOR OLIVINE DEFORMATION MECHANISM IN A COLD AND DRY SUBDUCTING CONTINENTAL SLAB - Xu Z.; Zeng L.; Yang J.; Chen F.; Liang F.; Wang Q.; Ji S.; Chen J.; Wenk H.-R. (My University, 2006)
Lattice-preferred orientations (LPO) of olivine, diopside, enstatite and garnet from the Zhimafang garnet peridotite body in the Sulu ultrahigh-pressure (UHP) metamorphic terrane (China) were measured using the electron backscatter diffraction (EBSD) technique. The peridotite was captured from a mantle wedge immediately adjacent the subducted Yangtze slab and then experienced the UHP metamorphism at 750–950 °C and 4–7 GPa. The olivine LPO is characterized by the [001] axis close to the stretching lineation and the (100) plane subparallel to the foliation, indicating the prevailing of (100) [001] slip. Enstatite LPO displays the dominance of (100) [001] slip. Diopside developed complex LPO patterns that are difficult to explain using a single slip system of (100) [001]. Garnet is almost randomly oriented due to its low volume fractions, cubic symmetry and the presence of numerous slip systems. Calculated seismic properties of the peridotite yield a maximum P-wave velocity normal to the foliation and a minimum along the foliation, with anisotropy up to 8% in strongly sheared samples. The S-wave velocity pattern is complex but the fast polarization plane generally normal to the foliation. The inferred shear sense from the olivine LPO is top-to-SE, in contrary to exhumation-induced top-to-NW thrusting recorded in the quartz LPO, implying that the olivine LPO formed at early UHP metamorphic conditions. The olivine crystals have relatively low water contents (141–475 H/106 Si), indicating a fluid-deficient environment for the LPO formation. The present study suggests that a combination of low temperature and UHP plays a much more